LOOK EAST: TOTAL QUALITY MANAGEMENT PRACTISED BASED ON JAPANESE APPROACH - Md. Fauzi Ahmad @ Mohamad (Penerbit UTHM, 2012)
This book is about comparing TQM practices between the Japanese and non-Japanese companies. Analysis were made to find significant difference in TQM practices and importance between Japanese and non-Japanese companies. The results showed that there are significant differences in TQM practices. Furthermore, Japanese companies have high perception on the importance of product development. The top five quality activities implemented are: quality control circle, supplier improvement, Failure Mode Effect Analysis (FMEA), Value Engineering (VE) and quality costing. The book also proposed Quality Improvement Guidelines (QIG) framework for TQM implementation. Management leadership, TQM awareness, standardization, customer satisfaction strategies and kaizen activities are five major parts in the framework. The framework is also supported by Critical Success Factors (CSFs) to ensure the success of TQM implementation. The framework is step by step and can assist companies in meeting customer satisfaction, employee satisfaction and business growth.